The South Africa 2010 FIFA World Cup: A Look Back: Perceptions of its Impact on Tourism in South Africa - Chuchu, Tinashe (International Review of Management and Marketing, 2021)
Africa’s first FIFA World Cup sparked a series of scholarly work mostly conducted prior to this event. This phenomena is still relevant today with many unanswered questions. This research therefore investigates and examines literature on how the 2010 FIFA World Cup is perceived almost a decade later. A qualitative approach was adopted based on secondary data sources and grey literature. Contextual information was gathered from popular data bases that include Science direct, Ebsco host, Emerald and Google scholar. A total of 20 studies on both tourism in South Africa and the 2010 FIFA World Cup published between 2004 and 2019 were examined and systematically presented and discussed. Recurring trends based on review of literature were identified. The destination image theory and the destination concept were used to comprehend international visitors’ attitudes and their interpretation of South Africa as a travel destination. One of key findings was that the crime in South Africa, before, during after the World Cup ranks highest in terms of tourism deterrence. However, the event was generally perceived positive as a fairly positive success with room for socio-economic improvement. Implications were provided and possible areas of further were suggested with additional questions presented. Keywords: Destination marketing, Africa’s World Cup, Tourism, South Africa JEL Classifications: M31, L83 DOI: https://doi.org/10.32479/irmm.11593